Integrating the Doctrine of Creation (Creatio Ex Nihilio) in Christian Religious Education for Primary Students in Indonesia: A Biblical-Pedagogical Framework - Silitonga, Roedy; Elizabeth, Andrea Ratu; Yarona, Neli Blandina (PEADA': Jurnal Pendidikan Kristen, 2025)
The teaching of scientific theories of origins, such as the Big Bang and evolution, in primary education often creates epistemological tension with biblical teaching, particularly within Christian school contexts. In Indonesia, this tension is frequently addressed without a clear pedagogical framework that integrates faith and learning coherently. This study aims to develop a biblical–pedagogical framework for integrating the doctrine of creation (creatio ex nihilo) within Christian Religious Education (CRE) for primary students. Employing a qualitative research design through literature analysis and classroom-based case studies in Indonesian Christian primary schools, this study examines how the doctrine of creation can be taught as divine revelation rather than as a competing scientific explanation. The findings indicate that when creation is presented theologically as an act of God’s sovereign will, students engage scientific knowledge critically while maintaining biblical authority as the foundation of learning. This study proposes a biblical–pedagogical framework that positions Christian teachers as facilitators, reconcilers, and transformers in guiding students toward an integrated understanding of faith and knowledge. The framework contributes to Christian education by offering a coherent model for faith–learning integration that supports intellectual formation and spiritual growth among primary students in Indonesia.